The construction of 'ordinariness' across media genres - Fetzer, Anita, 1958-; Weizman, Elda (Pragmatics & beyond ;, 2019)
"Departing from the premise that 'being ordinary' is brought into the discourse and brought out in the discourse and is thus an interactional achievement, the contributions to this edited volume investigate its construction, reconstruction and deconstruction in media discourse. Ordinariness is perceived as a scalar notion which is conceptualised against the background of both non-ordinariness and extra-ordinariness. The chapters address its strategic construction across media genres (public talk, Prime Minister's Questions, interview, radio call-in, commenting) and discursive activities (tweets, social media posts) as done in various languages (American English, Austrian German, British English, Chinese, French, Finnish, Hebrew and Japanese) by professional participants (e.g., politicians, journalists, scientists) and by ordinary people participating in media discourse (e.g., ordinary citizens, viewers, members of the audience). Discursive strategies used to bring about (non/extra) ordinariness include small stories, quotations, conversational style, irony, naming and addressing as well as references to the private-public interface"--